DESAIN INTERIOR RUMAH TINGGAL MIKRO SEBAGAI DAMPAK ADAPTASI KEBIASAAN BARU DI MASA NEW NORMAL - Ahmad Fajar Ariyanto; Indarto Indarto (Texture:Art and Culture Journal, 2021)
This research takes the title Reprogramming Interior of Micro Houses as the Impact of Adapting New Habits in the New Normal Era. This applied research as an effort to reprogram the interior of residential houses,especially homes with limited land (micro houses) is an urgent verb to be carried out immediately to savethe smallest environment in the community against the dangers of a pandemic and the possibility of further outbreak movements.The problem formulation in applied research is 1) Why is interior reprogramming as a result of changes in human behavior in the new normal era needed to prevent the transmission of Covid 19 in the community? 2) How is interior design thinking reprogramming to find the basic concepts of residential interiors that are in accordance with the adaptation of habits in the new normal era? and 3) How is the interior design of residential houses in the new normal era? The purpose of the research is to find the concept of interior programming as a basis for planning residential interiors that are in accordance with the adaptation of new habits and COVID 19 health protocols in the New Normal era. This applied research is a qualitative research with analytical descriptive with design thinking approach. The designsolving approach uses a functional, ergonomic, technical and Covid 19 health protocol approach that is centered on the user center or users. The results of the research that will be achieved in interior design are: identification of the causes and needs for Reprogramming Interior of Micro Residential Houses as the Impact of Adapting New Habits in the New Normal era.